Intestinal epithelial cell apoptosis due to a hemolytic toxin from Vibrio vulnificus and protection by a 36 kDa glycoprotein from Rhus verniciflua Stokes. (March 2019) - Lee, Young-Min; Park, Jong Pil; Lim, Kye-Taek; Lee, Sei-Jung
Abstract: Rhus verniciflua stokes (RVS) has been used as a functional food to cure inflammatory diseases in Korea. In the present study, we carry out an investigation of the cellular mechanism of a 36 kDa glycoprotein isolated from RVS fruit (RVS glycoprotein) during the apoptosis of human gastrointestinal epithelial HCT116 cells induced by the hemolytic toxin (VvhA) produced by V. vulnificus . Recombinant protein (r) VvhA produced by V. vulnificus stimulated apoptosis by activating the phosphorylation of protein kinase C (PKC) through the production of intracellular reactive oxygen species (ROS). However, RVS glycoprotein significantly inhibited the level of ROS production and PKC activation in rVvhA-stimulated HCT116 cells. Interestingly, we found that RVS glycoprotein has inhibitory effects on the phosphorylation of c-Jun N-terminal kinase (JNK) and nuclear factor-kappa B (NF-κB), which are responsible for the expression of Bax and cleaved caspase-3 in HCT116 cells treated with rVvhA, respectively. On the basis of these results, we suggest that RVS glycoprotein blocks mitochondrial apoptotic cell death induced by rVvhA via the inhibition of ROS-mediated signaling events in HCT116 cells. Highlights: RVS glycoprotein blocks cell death induced by V. vulnificus, VvhA. RVS glycoprotein reduces ROS production to recover cell death induced by rVvhA. RVS glycoprotein suppresses PKC/JNK/NF-κB pathway activated by rVvhA. RVS glycoprotein inhibits expression of Bax and cleaved-caspase 3 induced by rVvhA.